Resili(g)ence. Smart Cities / Resilient Landscape - Manuel Gausa (Agathón)
The holistic approach to the contemporary city recalls the use of new complex and integrated techno-environmental tools and qualitative urban development policies, in positive synergy. Advanced, proactive and reactive responses, which move in a hybrid field: on the one hand prevention and mitigation of conflicts and urban-territorial stress situations, through the interconnection of systematized data; on the other the programming of strategic interventions, articulated in intertwined systems. The term Resili(g)ence combines ‘intelligent values’ (information, knowledge, projection and adaptation) with ‘resilient values’ (resistance and recycling, recovery, renewal or adaptation) in a new responsive, sensory, and sensitive condition.